Analysis of halal tourism development strategy in East Java Province - Carollina, Riska; Triyawan, Andi (Journal of Islamic Economics Lariba, 2018)
The tourism sector is one of the sectors that is of great importance to the Indonesian economy. On the other hand, the second world population and Indonesia's income are Muslim, from the same thing. This research was carried out in the province of East Java, which is a province that has diversity and natural resources compared to other provinces. So the purpose of this research is to find out the meaning of the concept in accordance with the Qur'an and Hadith. The method used is a qualitative approach with the SWOT analysis method. The data used is primary data obtained through interviews, documentation and documentation. The results of this study indicate that if there is an increase in Indonesia, especially in the province of East Java, it has not developed well. This is caused by the amenities or facilities in the perfect place. In addition, various technologies and aspects to develop halal are still not synergized well. Therefore, an appropriate strategy is needed to develop halal, especially in East Java.